Design and development of an automated robot for collecting latex cups in rubber plantation. Issue 1 (December 2021) - Kang, S. J.; Wong, C.S.; Lim, C.H.; Tan, Y. C.
Abstract: The main reason for robots in agriculture are saving the time and energy required for performing repetitive tasks and increasing the productivity. The turnover rate in rubber plantation is high and youngster nowadays refuse to work in this industrial. This project aims to build a small-scaled automated robot prototype for collecting latex cups in hopes to reduce the dependency of labor in collecting latex. It was fabricated by using 3D printer and consists of transmission system, linear actuator robotic arm and a storage tank. It was analyzed through static test and balance test for mechanical stability. The robot developed can perform auto-navigation with proper calibration on the transmission at flat terrain, and able to control the 3 Degree of Freedom (DoF) robotic arm on the prototype to grab the latex cup smoothly. Ultrasonic sensors are used to locate the rubber trees and movements of the prototype. The robotic arm and the base are controlled by an Arduino Uno and motor driver circuit respectively. A magnetometer was implemented to ensure the prototype could move straight throughout the process. During test, the prototype was placed in front of two "rubber trees" (imitated by water bottle) to let it retrieves the model latex cups and extract the liquid inside. The results showed that implementation of magnetometer enabled the robot much more consistent in the moving direction and proper delay time used for the navigation of the robot. The prototype is able to automate basic tasks and act as fundamental design for future development.